Block diagonalisation with adaptive resource allocation algorithm for multi-user MIMO-OFDM systems. (17th June 2009) - Gunaseelan, K.; Reba, P.; Kandaswamy, A.
The challenging issue in multi-user MIMO-OFDM system is to cancel multi-access interference (MAI) when different users share the same subcarrier. Also, the presence of MAI makes the resource allocation problem very complicated. Hence it is essential to find the optimal transmit and receive weight vectors, to reduce MAI and to adaptively assign resources to meet the quality of service (QoS) requirements. In this paper, block diagonalisation (BD) with waterfilling power allocation is considered and analysed their performance. This BD with waterfilling power allocation algorithm increases the system capacity with zero MAI. In order to have further increase in system performance, the proposed method considers rate adaptation scheme and margin adaptation scheme. In rate adaptation technique BD with power and subcarrier allocation is performed to maximise the system capacity. In margin adaptation technique BD with power and bit allocation is done to improve QoS of the system. The simulation results show that there is significant improvement in system performance also guaranteeing zero MAI.